Outpatient management of severe ovarian hyperstimulation syndrome: a systematic review and a review of existing guidelines. (3rd April 2018) - Gebril, Amr; Hamoda, Haitham; Mathur, Raj
Abstract: Ovarian hyperstimulation syndrome (OHSS) is a potentially serious complication of assisted reproductive treatment. Management of women with severe OHSS has traditionally included hospitalisation for close monitoring and supportive treatment. The aim of this review is to assess the evidence for safety and efficacy of outpatient management of severe OHSS. A systematic review of studies describing outpatient management options was performed. Current guidance from advisory bodies was also reviewed. Outpatient management has been found in observational studies to be safe and cost-effective compared to inpatient management. Paracentesis of ascitic fluid seems to be effective treatment for severe OHSS along with supportive management including maintenance of fluid balance and preventative measures against thrombo-embolism. GnRH antagonist was shown in few studies to be effective in treatment of early severe OHSS although further research is required to assess its role in this context. Appropriate outpatient set up and protocols are essential to provide safe outpatient management for women with severe OHSS.